2020
DOI: 10.1021/acsami.0c00370
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Mild Cognitive Impairment and Alzheimer’s Disease by the Plasma and Serum Amyloid-beta 42 Assay through Highly Sensitive Peptoid Nanosheet Sensor

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder with a continuous pathophysiological process starting from the preclinical and mild cognitive impairment (MCI) phases to the dementia phase. Early diagnosis is prerequisite for the early intervention of AD but meanwhile challenging. Amyloid-beta 1−42 (Aβ 42 ) plays a crucial part in AD pathology. Positron-emission tomography (PET) imaging of Aβ 42 in the brain and the measurement of Aβ 42 in the cerebrospinal fluid (CSF) have been adopted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…Mild cognitive impairment (MCI) is universally considered as the predementia phase of Alzheimer's disease (AD) (Gao et al, 2020 ). About one in five community-dwelling elders aged 65 years and above suffer from MCI (Livingston et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mild cognitive impairment (MCI) is universally considered as the predementia phase of Alzheimer's disease (AD) (Gao et al, 2020 ). About one in five community-dwelling elders aged 65 years and above suffer from MCI (Livingston et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our ROC analysis revealed that the d -glutamate level for all patients with MCI versus healthy controls determined an optimal cut-off value (1374.49), with a good sensitivity (0.905) and specificity (0.613; AUC = 0.816), whereas the ROC analysis revealed that the d -glutamate level for all patients with AD versus healthy controls determined an optimal cut-off value (971.56), with a moderate sensitivity (0.632) and a good specificity (0.968; AUC = 0.839). Studies have investigated peripheral blood biomarkers to predict MCI and AD (Gao et al, 2020; Su et al, 2019; Xie et al, 2020). A recent meta-analysis reported that patients with MCI or AD had lower brain-derived neurotrophic factor (BDNF) levels than did healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…AD is associated with a specific onset and course of cognitive and functional decline during ageing, together with aggregation of a particular Aβ with hyperphosphorylated tau protein that causes loss of synapses and neurodegeneration [54,55]. Aβ, the level of which is associated with the extent of cognitive decline [56], is measured in the cerebrospinal fluid and brain for purposes of auxiliary diagnosis [57].…”
Section: Discussionmentioning
confidence: 99%